Service Quality and Perceived Value as Determinants of Word of Mouth via Santri Satisfaction: A Study of Islamic Boarding Schools in Jombang Regency - Mahendri, Wisnu; Astuti, Widji; Arifin, Syaiful (International Journal of Scientific Research and Management (IJSRM), 2024)
In the era of increasingly tight educational competition, word of mouth is a vital key element in the strategy of developing educational institutions. In the Islamic boarding school education environment, there are various factors that influence word of mouth, the most important of which are service quality and perceived value. The purpose of the study was to analyze the role of student satisfaction in mediating service quality and perceived value in terms of word of mouth at Islamic boarding schools in Jombang Regency. This is a quantitative study with a causality design. Students from five major Islamic boarding schools in Jombang Regency, specifically Darul Ulum, Mambaul Ma'arif, Tebuireng, Tarbiyatun Nasyiin, and Bahrul Ulum Islamic Boarding Schools, comprise the population. The analysis tool, SEM AMOS, yielded a sample size of 200 respondents. The results of the study revealed that service quality and perceived value affect word of mouth through student satisfaction. To generalize the findings, we still need to develop variables that influence word of mouth; additionally, we need to conduct research with different objects, not only in the Islamic boarding school education industry but also in other service industries.